Upaya Peningkatan Aktivitas Belajar Menggunakan Model Project Based Learning Pada Materi Komposisi dan Dekomposisi Bangun Datar Kelas IV Sekolah Dasar - Hutami, Cahya Amalia; Kurniawati, Wahyu; Danuri, Danuri (Paedagogie, 2024)
The purpose of this study is to demonstrate how the use of tangram learning materials in the Project Based Learning (PJBL) paradigm can enhance students' learning activities in the mathematics topic of flat shape construction and decomposition. This article describes a type of research known as Classroom Action Research (PTK), in which 17 research participants from class IV pupils at Sembungan State Elementary School participated in two cycles of action during the academic year 2023–2024. The average proportion of learning activities grew from 63.441% in cycle I to 75.176% in cycle II, according to the results of the observations. After taking action in cycle II, there was a notable increase. This research demonstrates how well project-based learning with the aid of tangram media improves student learning outcomes, which are directly tied to what students learn during class.